What the Army needs to know to align its operational and institutional activities - Camm, Frank A., 1949-; Cook, Cynthia R., 1965-; Masi, Ralph; Wong, Anny, 1968-; Rand eBooks (Santa Monica, CA : RAND, 2007)
As the U.S. Army transforms its operating force, inevitably the institutional Army-the "generating force" that fills and sustains the Army's combat units-must change as well. The Army must transform its institutional activities to (1) align them with operating forces in ways that improve support, and (2) release resources from institutional activities that the Army can use to add new brigades and weapon systems. This document describes a way for the Army leadership to negotiate and establish performance goals for institutional activities that give the Army effective control over the alignment of its operational and institutional elements while preserving flexibility and initiative within institutional activities to choose how to meet these goals. It assesses value chains to map how the institutional Army transforms resources into outputs that it delivers to the operating force to support desired outcomes, and also illustrates how to evaluate value chains relevant to three representative institutional Army activities: medical services, enlisted accessioning, and short-term acquisition. It then derives implications for (1) integrating such an approach with the Army's ongoing Strategic Management System and Lean Six Sigma initiatives, and (2) identifying the additional empirical data needed to allow such integration.
"RAND Arroyo Center."
Includes bibliographical references (p. 271-280).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Army -- Reorganization; Military planning -- United States; Electronic books